Whole‐brain arteriography and venography: Using improved velocity‐selective saturation pulse trains. Issue 4 (10th August 2017) - Li, Wenbo; Xu, Feng; Schär, Michael; Liu, Jing; Shin, Taehoon; Zhao, Yansong; van Zijl, Peter C.M.; Wasserman, Bruce A.; Qiao, Ye; Qin, Qin
Abstract : Purpose: To develop velocity‐selective (VS) MR angiography (MRA) protocols for arteriography and venography with whole‐brain coverage. Methods: Tissue suppression using velocity‐selective saturation (VSS) pulse trains is sensitive to radiofrequency field (B1 +) inhomogeneity. To reduce its sensitivity, we replaced the low‐flip‐angle hard pulses in the VSS pulse train with optimal composite (OCP) pulses. Additionally, new pulse sequences for arteriography and venography were developed by placing spatially selective inversion pulses with a delay to null signals from either venous or arterial blood. The VS MRA techniques were compared to the time‐of‐flight (TOF) MRA in six healthy subjects and two patients at 3T. Results: More uniform suppression of stationary tissue was observed when the hard pulses were replaced by OCP pulses in the VSS pulse trains, which improved contrast ratios between blood vessels and tissue background for both arteries (0.87 vs. 0.77) and veins (0.80 vs. 0.59). Both arteriograms and venograms depicted all major cervical and intracranial arteries and veins, respectively. Compared to TOF MRA, VS MRA not only offers larger spatial coverage but also depicts more small vessels. Initial clinical feasibility was shown in two patients with comparisons to TOF protocols. Conclusion: Noncontrast‐enhanced whole‐brain arteriography and venography can be obtained without losing sensitivity to small vessel detection. Magn Reson Med 79:2014–2023, 2018. © 2017 International Society for Magnetic Resonance in Medicine.